The ANDEEP Tanaidacea (Crustacea: Peracarida) revisited II: the family Anarthruridae and family incertae sedis, with descriptions of three new species and the erection of a new genus - Larsen, Kim (Zootaxa, 2013)
Specimens collected during the ANDEEP I and II expeditions revealed three new species belonging to the family Anarthruridae and family incertae sedis. One new species of Anarthruridae, Ithyomus antarcticus n. sp. is described. Also described are two new species belonging to genera currently not assigned to a family; one in the genus Parafilitanais (P. denticulus n. sp.) and one in Pseudoarthrura (P. tuberculata n. sp.). The genus Cristatotanais is removed from Anarthruridae, while P. setoserrata is removed from Pseudoarthrura and elevated to genus rank under the name Selvagentanais gen. nov.